INVESTIGATING APPROPRIATE USAGE OF SELF-MENTIONS IN CONCLUSION SECTIONS OF RESEARCH ARTICLES: A CORPUS-BASED STUDY - Iram Soomro; Dr. Tania Laghari; Dr. Abdullah Laghari; Ali Bux Khoso (International Journal of Contemporary Issues in Social Sciences, 2024)
The abstract is a most important part of any research study. It gives an outlook of the whole study, it answers what the whole research is about, and gives readers insights to decide whether to read or leave the study. So, this study aimed to identify the appropriate usage of personal pronouns in conclusion sections of research articles of two social sciences’ discipline, sociology and linguistics. Its main purpose is to analyze the usage of personal pronouns in each discipline individually, and then it compares the usage in both disciplines. For this, corpus of 50 research articles, twenty-five conclusion sections written in sociology with 21667 numbers of tokens and twenty-five conclusion sections written in linguistics articles with 19670 token numbers were included in the research. In addition to that, Ken Hyland’s Interdisciplinary Model of Metadiscourse is applied to analyze the data. Furthermore, the study also analyzes the raw and normalized frequency of each pronoun with the help of a software application called ‘Antconc’. The results of the study show how literary scholars use self-mentions in their articles to persuade the readers’ attention and to get personally engaged within the study. The results also demonstrated that the writers mostly use first-person plural pronoun “We” in the articles not only to show their collective efforts they put in the research but also to position themselves within the text.